EVEKTIFITAS PENERAPAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION DISERTAI MEDIA TREE CHART TERHADAP PERKEMBANGAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 2 RANAH BATAHAN - Safitra, Armi; Mukhni, Mukhni; K, Delsi (STKIP PGRI Sumbar, 2013)
Students comprehension of mathematical concepts are relatively low is underlying done this research. The purposes research is to increase students comprehension of mathematical concepts with models of cooperative learning Type group investigation with the media three charts in seventh grade. This type of research is the study of the random experiment with the design of the subject. From the results of the study concluded that students comprehension of mathematical concepts with Cooperative Learning Type Group Investigation and also Three Charts MediaÂ models has increased.